Mutant Ataxin-2 expression in aged animals aggravates neuropathological features associated with Spinocerebellar Ataxia type 2 - Afonso, Inês T. (2022)
Spinocerebellar ataxia type 2 (SCA2) is a rare autosomal, dominantly inherited disease, in which the affected individuals have a disease onset around their third life decade. The molecular mechanisms underlying SCA2 are not yet completely understood, for which we hypothesize that aging plays a role in SCA2 molecular pathogenesis. In this study, we performed a striatal injection of mutant ataxin-2 mediated by lentiviral vectors, in young and aged animals. Twelve weeks post-injection, we analyzed the striatum for SCA2 neuropathological features and specific aging hallmarks. Our results show that aged animals had a higher number of mutant ataxin-2 aggregates and more neuronal marker loss, compared to young animals. Apoptosis markers, cleaved caspase-3, and cresyl violet staining also indicated increased neuronal death in the aged animal group. Additionally, mRNA levels of microtubule-associated protein 1 light-chain 3B (LC3) and sequestosome-1 (SQSTM1/p62) were altered in the aged animal group, suggesting autophagic pathway dysfunction. This work provides evidence that aged animals injected with expanded ataxin-2 had aggravated SCA2 disease phenotype, suggesting that aging plays an important role in SCA2 disease onset and disease progression.